2023
DOI: 10.3389/fpsyg.2022.1079848
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning buffers the consequences of the COVID-19 pandemic for children’s quality of life and loneliness

Abstract: COVID-19 resulted in mass quarantine measures early in the pandemic. This disruption of daily life widened inequities and made children one of the most vulnerable populations during the crisis. This national, cross-sectional “COVID-Kids” study collected data from almost 500 parent–child dyads using standardized measures to better understand the effects of COVID exposure and impact on children’s quality of life and loneliness. Data were collected via social media from May to July 2020. According to parent proxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…As hypothesized, children from parents who perceived a greater negative impact and/or a lower positive impact of the pandemic on their daily lives, showed higher levels of anger, anxiety, depressive symptoms and sleep problems as well as lower levels of positive affect and self-regulation. These findings align with studies examining families with children from a broader age range [ 19 , 20 , 22 ]. This may be explained by parental behaviors towards the child; if the parent had a negative perception of the pandemic, the parent may have—either directly or indirectly—expressed negative thoughts or feelings regarding the pandemic towards the child, which in turn impacted the child’s view on the pandemic and their well-being.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As hypothesized, children from parents who perceived a greater negative impact and/or a lower positive impact of the pandemic on their daily lives, showed higher levels of anger, anxiety, depressive symptoms and sleep problems as well as lower levels of positive affect and self-regulation. These findings align with studies examining families with children from a broader age range [ 19 , 20 , 22 ]. This may be explained by parental behaviors towards the child; if the parent had a negative perception of the pandemic, the parent may have—either directly or indirectly—expressed negative thoughts or feelings regarding the pandemic towards the child, which in turn impacted the child’s view on the pandemic and their well-being.…”
Section: Discussionsupporting
confidence: 87%
“…Many parents perceived the impact of the societal measures regarding COVID-19—e.g., working from home while taking care of the children, financial stress, job loss, feelings of isolation—as negative [ 19 21 ]. This parent-reported negative impact of COVID-19 was related with children’s lower quality of life and increased loneliness [ 22 ]. Parents, however, also reported a positive impact of the pandemic, in terms of more family-time spent together and more appreciation of family relationships [ 23 ], which may buffer children’s mental health.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on Chinese vocational students, poor family functioning leaded to increased mental health symptoms such as anxiety and depression while good family functioning was associated with improved well-being (Pan et al, 2020). Skeens et al (2023) found that parental distress predicted worsened quality of life and loneliness of American youth under the pandemic. Combining these literature, findings of this study highlight the importance of promoting the positive family functioning in university students under the pandemic.…”
Section: Family Functioning and Mental Healthmentioning
confidence: 99%